Dengue Fever Prevention Behavior at the Household Level in High and Low Incidence Areas: A Cross-Sectoral Comparative Study in the Tropics - Budi Joko Santosa; Agung Suharto; Nurlailis Saadah; Heru Santoso Wahito Nugroho; Sunarto Sunarto; Suparji Suparji; Alfi Rusdianti (Health Dynamics, 2026)
Background: Dengue fever remains a major public health concern in tropical regions, including Indonesia. Household-level knowledge, attitudes, and practices (KAP) play a critical role in sustainable vector control. This study aimed to compare KAP regarding dengue prevention among household heads in high- and low-incidence areas in Magetan Regency, Indonesia. Methods: A cross-sectional comparative study was conducted among 785 household heads selected using stratified random sampling. A total of 390 respondents were recruited from high-incidence areas (≥11 cases/year) and 395 from low-incidence areas (≤10 cases/year). Data were collected using a validated and reliable structured questionnaire measuring knowledge (45 items), attitudes (18 items), and practices (25 items). Spearman rank correlation was used to examine associations between sociodemographic factors and KAP scores, and the Mann–Whitney U test was applied to compare differences between groups. Results: Knowledge and attitude scores did not differ significantly between high- and low-incidence areas (p > 0.05). However, prevention practice scores were significantly higher in high-incidence areas (Mean = 15.51; SD = 4.37) compared to low-incidence areas (Mean = 12.94; SD = 5.91; p < 0.001). Age was positively associated with attitudes and practices in both areas, while education level was significantly correlated with knowledge. Employment status was associated with prevention practices, whereas gender showed no significant association with KAP. Conclusions: Dengue prevention practices were stronger in high-incidence areas, suggesting that direct exposure to disease risk influences behavioral responses more than knowledge alone. Strengthening community empowerment and behavior-focused interventions is essential, particularly in low-incidence areas, to enhance preparedness and prevent future outbreaks.